Mechanical properties of calcium carbonate and coconut shell filled polypropylene composites - Mehdi Heidari, 1984-; Wan Aizan Wan Abdul Rahman, supervisor; Fakulti Kejuruteraan Kimia (2012)
Thesis (Sarjana Sains (Teknologi Polimer)) - Universiti Teknologi Malaysia, 2012